Salt intake and gastric cancer: a pooled analysis within the Stomach cancer Pooling (StoP) Project - Morais, Samantha; Costa, Adriana; Albuquerque, Gabriela; Araújo, Natália; Pelucchi, Claudio; Rabkin, Charles S.; Liao, Linda M.; Sinha, Rashmi; Zhang, Zuo-Feng; Hu, Jinfu; Johnson, Kenneth C.; Palli, Domenico; et al. (Cancer causes & control, 2022)
Purpose Previous studies show that consuming foods preserved by salting increases the risk of gastric cancer, while results on the association between total salt or added salt and gastric cancer are less consistent and vary with the exposure considered. This study aimed to quantify the association between dietary salt exposure and gastric cancer, using an individual participant data meta-analysis of studies participating in the Stomach cancer Pooling (StoP) Project. Methods Data from 25 studies (10,283 cases and 24,643 controls) from the StoP Project with information on salt taste preference (tasteless, normal, salty), use of table salt (never, sometimes, always), total sodium intake (tertiles of grams/day), and high-salt and salt-preserved foods intake (tertiles of grams/day) were used. A two-stage approach based on random-effects models was used to pool study-specific adjusted (sex, age, and gastric cancer risk factors) odds ratios (aORs), and the corresponding 95% confidence intervals (95% CI). Results Gastric cancer risk was higher for salty taste preference (aOR 1.59, 95% CI 1.25–2.03), always using table salt (aOR 1.33, 95% CI 1.16–1.54), and for the highest tertile of high-salt and salt-preserved foods intake (aOR 1.24, 95% CI 1.01–1.51) vs. the lowest tertile. No significant association was observed for the highest vs. the lowest tertile of total sodium intake (aOR 1.08, 95% CI 0.82–1.43). The results obtained were consistent across anatomic sites, strata of Helicobacter pylori infection, and sociodemographic, lifestyle and study characteristics. Conclusion Salty taste preference, always using table salt, and a greater high-salt and salt-preserved foods intake increased the risk of gastric cancer, though the association was less robust with total sodium intake.